Pengaplikasian Kayu Apu (Pistia stratiotes L) Dalam Menurunkan Kadar BOD, COD dan TSS Pada Limbah Cair Laboratorium Di RSUD Besuki Kabupaten Situbondo - Sari, Sudiana Vurigga (Jurnal Keperawatan Profesional, 2020)
Hospital Laboratory wastewater contains organic compounds with a high enough concentration and possibly contain other chemical compounds and pathogenic microorganisms that can cause disease to the surrounding community. A way to overcome this problem is to do hospital laboratory liquid waste treatment. One alternative that can be used is the phytoremediation method using apu wood plants. Research on decreasing levels of BOD, COD and TSS in Besuki Public Hospital laboratory wastewater using Apu Wood (Pistia stratiotes L) was carried out in January - March 2019 with the aim to determine the decrease in laboratory wastewater BOD, COD and TSS after being given Apu (Pistia stratiotes L). The method used in treating liquid waste laboratory is phytoremediation. The results showed that after being treated as many as 10 treatments with the contact time of the apple plant for 1 day, 3 days and 6 days there was a significant decrease in BOD levels in the treatment with indigo P = 0,000 <0,05 for COD levels based on ANOVA output, known the value based on Anova sig table results is 0,000 <0,05 so it can be concluded that the average COD level after being treated is "DIFFERENT" significantly while the TSS parameter is ANOVA test with sig value 0,309> 0,05 which means "NO DIFFERENCE "Significantly on the treatment. It is recommended for further research, it should be endeavored to use plants that have resistance to waste, especially for contact time so that they can use higher waste concentrations with longer contact times. Keywords: BOD, COD, TSS, Apu Wood Plant (Pistia stratiotes L